2010
DOI: 10.5194/acp-10-239-2010
|View full text |Cite
|
Sign up to set email alerts
|

Physical and optical properties of aerosols over an urban location in Spain: seasonal and diurnal variability

Abstract: Abstract. Measurements of aerosol optical properties and aerosol number size distribution obtained during the period from December 2005 to November 2007 at Granada, an urban site in south-eastern Spain, are analyzed. Large variations of the measured variables have been found, and related to variations in emissions sources and meteorological conditions. High values of aerosol absorption and scattering coefficients are obtained during winter and low values are measured during summer. This seasonal pattern in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
107
4
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(143 citation statements)
references
References 66 publications
16
107
4
4
Order By: Relevance
“…Main local aerosol sources are road traffic, soil re-suspension (especially during the warm-dry season) and domestic heating based on fuel-oil combustion during winter (Titos et al, 2012, Titos et al, 2014a. Main external aerosol sources are the Sahara Desert located at 500 km southward as well as industrial and urban areas in Europe (Lyamani et al, 2010).…”
Section: Experimental Sitementioning
confidence: 99%
“…Main local aerosol sources are road traffic, soil re-suspension (especially during the warm-dry season) and domestic heating based on fuel-oil combustion during winter (Titos et al, 2012, Titos et al, 2014a. Main external aerosol sources are the Sahara Desert located at 500 km southward as well as industrial and urban areas in Europe (Lyamani et al, 2010).…”
Section: Experimental Sitementioning
confidence: 99%
“…Atmospheric aerosol optical properties have been widely investigated in the city of Granada at surface level (e.g., Lyamani et al, 2008;Lyamani et al, 2010;Titos et al, 2012;Segura et al, 2014), in the vertical column with height resolution (e.g., GuerreroRascado et al, 2008;Alados-Arboledas et al, 2011;Bravo-Aranda et al, 2015 and references therein) and column-integrated (e.g., Lyamani et al, 2005;Valenzuela et al, 2012). The meteorological conditions together with the topography of the city sited in a valley surrounded by mountains of high elevation (about 3500 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%
“…In Valencia (Spain), maximum AOD values were observed (between 2002-2005) from June to September, whereas the minimum values occurred from October to February (mainly in December and January) (Estellés, 2008). Behnert et al (2004) Granada (Spain), M'Bour (Senegal), Gwangju (Korea) and Thessaloniki (Greece) also show high AOD values in summer and low values in winter (Meleti and Cappellani, 2000;Kim et al, 2006;Kazadzis et al, 2007;Léon et al, 2009;Lyamani et al, 2010). (The latitude and longitude of the places mentioned in this article can be found in Table 2.…”
Section: Seasonal and Monthly Variabilitymentioning
confidence: 99%
“…Both Bäumer et al (2008) and Xia et al (2008) reported a weekly cycle in AOD for Central Europe (45-55 • N; 0-20 • E). Seasonal patterns in AOD with maximum values in spring and summer and minimum values in autumn and winter are observed in many studies (Meleti and Cappellani, 2000;Behnert et al, 2004;Kim et al, 2006;Estellés, 2008;Remer et al, 2008;Che et al, 2009;Léon et al, 2009;Lyamani et al, 2010). Gröbner and Meleti (2004) studied long-term trends in AOD at Ispra and detected a decrease between 1991 and 1997, followed by a stabilization in the AOD values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation